Pengaruh Influencer Marketing, Sosial Media Dan Daya Tarik Iklan Dalam Meningkatkan Brand Awarenees Platform Tokopedia (Studi Kasus Pada Mahasiswa Unisma Jurusan Manajemen Angkatan 2021) - Fadhilah, Rio; Arifin, Rois; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze the influence of Influencer Marketing, Social Media, and Advertising Appeal in enhancing Brand Awareness of the Tokopedia platform. The application of Influencer Marketing, Social Media, and Advertising Appeal in each of these variables not only contributes individually but also collectively in shaping Brand Awareness and consumer behavior in an increasingly competitive digital competition era. The research method used in this study is a quantitative approach with data collection techniques in the form of an online questionnaire distributed to 87 respondents, specifically Management students from the Class of 2021. The results of this study indicate that Influencer Marketing has a positive and significant effect on increasing Brand Awareness, Social Media has a positive and significant effect on Brand Awareness, and Advertising Appeal has a positive and significant effect on Brand Awareness. The implications of this research explain that the Tokopedia platform needs to implement Influencer Marketing to disseminate information and utilize appropriate social media, as well as to enhance the appeal of the advertisements being distributed, which will significantly impact the increase in brand awareness in the minds of consumers.   Keywords: Influencer Marketing, Social Media, Advertising Appeal, Brand Awareness, Tokopedia Platform.